2021
DOI: 10.21037/atm-20-5698
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnification correction in macular vessel density assessment: a contralateral eye study in anisometropia patients

Abstract: Background: Investigating the impact of magnification correction in macular vessel density using optical coherence tomography angiography (OCTA) in patients with anisometropia.Methods: Cross-sectional study. Totally 47 patients (11 male, 36 female) aged >18 years with high myopia were analyzed. All patients underwent evaluation of visual acuity, subjective refraction, and axial length. Anisometropia (n=37) was defined as a refraction difference between paired eyes ≥0.75 D. The control group (n=10) consisted pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…The magnification correction of AL does affect the measurement of CC FD%, especially in myopic patients, as has been demonstrated in previous studies. [63][64][65][66] In OCTA, the 6 × 6 mm 2 scan area was calculated from the linear distance from the retinal surface, extending at an angular size of approximately 20° × 20°. The default AL was used for OCT measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The magnification correction of AL does affect the measurement of CC FD%, especially in myopic patients, as has been demonstrated in previous studies. [63][64][65][66] In OCTA, the 6 × 6 mm 2 scan area was calculated from the linear distance from the retinal surface, extending at an angular size of approximately 20° × 20°. The default AL was used for OCT measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In the bright adaptation experiment, the [23] amplitudes of the a-wave and b-wave positively correlated with the FAZ and negatively correlated with the FVD. Lastly, the OP wave amplitude was positively correlated with the super cial macular blood ow density.…”
Section: Correlation Of Macular Microcirculation Macular Structure and Electrophysiological Function In People With High Myopiamentioning
confidence: 88%
“…However, the results of research into the patterns and mechanisms of FAZ area changes in high myopia are inconclusive [6] . During the process of high myopic axial lengthening, the eyeballs do not uniformly expand to maintain the spherical shape [22]; the difference in the length of the high myopia axis leads to different degrees of optical magni cation, and current OCTA equipment does not provide correction methods [23]. This may affect the accuracy of the FAZ area of highly myopic eyes, resulting in discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that SVD and DVD in the macular area decreased with the stretching of AL ( Yang et al, 2020 ). Furthermore, differences in image magnification due to different ALs will affect vascular density ( Sampson et al, 2017 ; Fu et al, 2021 ). The scanning range of the SS-OCT/OCTA we applied can correct the difference in fundus magnification due to the different Als, to reduce the intervention of AL on the results of this study.…”
Section: Discussionmentioning
confidence: 99%